flying or digging? The trapdoor spider genus neocteniza pocock, 1895: Redescription of three species, new records from brazil, notes on natural history and first record of ballooning for idiopidae (araneae, mygalomorphae) - DE F. ROSSI, GIULLIA [UNESP]; GHIROTTO, VICTOR M. [UNESP]; GALLETI-LIMA, ARTHUR [UNESP]; INDICATTI, RAFAEL P. [UNESP]; GUADANUCCI, JOSÉ P.L. [UNESP] (Magnolia Press, 2021)
The Neotropical trapdoor spider genus Neocteniza Pocock, 1895 is distributed throughout Central and South America. The genus currently comprises 18 species and little is known about the biology of these spiders. We provide an amended diagnosis for the genus Neocteniza and the species: N. minima Goloboff, 1987, N. australis Goloboff, 1987 and N. toba Goloboff, 1987, and also redescribe them. We include new records of these species from Brazil and notes on natural history of N. toba, providing data on burrow structure, diet, development and the first record of ballooning behavior for Idiopidae. We propose a terminology for the genitalia and consider homology among genital structures and among possibly stridulatory structures. We also discuss relationships of Neocteniza with other Idiopidae, stressing the uniqueness of the genus and its differences from all other Idiopidae including other Genysinae.
Keywords: Atlantic Forest; Behavior; Cerrado; Genysinae; Haematodocha; Sexual dimorphism; Stridulatory apparatus